2017
DOI: 10.1507/endocrj.ej16-0243
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Japanese aldosterone-producing adenomas with KCNJ5 mutations

Abstract: PRIMARY ALDOSTERONISM (PA) has been reported to affect at least 6~10% of patients with essential hypertension [1][2][3][4][5] and is caused mostly by an adrenal adenoma (aldosterone-producing adenoma, APA) or by adrenal hyperplasia (idiopathic hyperaldosteronism, IHA). Although the tumorigenesis of APA remained unclear, somatic mutations of the potassium Characteristics of Japanese aldosterone-producing adenomas with KCNJ5 mutations Abstract. Somatic mutations in KCNJ5 gene have been identified in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 39 publications
(84 reference statements)
3
12
1
Order By: Relevance
“…Regarding KCNJ5 mutations, we and other groups from Western countries reported that patients with KNCJ5 mutations were younger and had high aldosterone levels [14, 15, 17, 33]. The current study also demonstrated that the mutation rate of the KCNJ5 gene in patients with APAs was 95% for those <50 years old, and this decreased to 67% in those ≥50 years old.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Regarding KCNJ5 mutations, we and other groups from Western countries reported that patients with KNCJ5 mutations were younger and had high aldosterone levels [14, 15, 17, 33]. The current study also demonstrated that the mutation rate of the KCNJ5 gene in patients with APAs was 95% for those <50 years old, and this decreased to 67% in those ≥50 years old.…”
Section: Discussionsupporting
confidence: 75%
“…We recently reported a very high frequency (~80%) of somatic mutations in the KCNJ5 gene in Japanese APAs [14–16]. In contrast, the prevalence of KCNJ5 mutations in APAs was found to be ~40% in Western countries [17].…”
mentioning
confidence: 99%
“…The majority of studies documenting the KCNJ5 genotype of APAs reported that patients harboring a KCNJ5 mutant APA were more commonly females, adrenalectomized at a younger age, with a larger tumor size than those harboring a KCNJ5 wild-type APA (1825, 34, 41). Though, some studies in Oriental cohorts had found no gender bias, as male and female APAs had similar KCNJ5 mutation rates (23, 2931, 33). In this study, males more commonly harbored a KCNJ5 mutant APA compared to females (39% vs. 23%) and there were no significant differences in age at adrenalectomy or tumor size between patients with a KCNJ5 mutant APA compared to patients with a KCNJ5 wild-type APA.…”
Section: Discussionmentioning
confidence: 99%
“…Monticone et al [ 8 ] reported that KCNJ5 -mutated APAs in Italy were composed mainly of fasciculata-like cells with higher CYP11B1 and lower CYP11B2 expressions than those in APAs of other causes. Okamura et al [ 9 ] found that KCNJ5 -mutated APAs in Japan had higher CYP11B2 and lower CYP11B1 mRNA levels than those without mutation. The APA in our patient expressed abundant CYP11B2 and scarce CYP11B1.…”
Section: Discussionmentioning
confidence: 99%